2017
DOI: 10.1186/s40834-017-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of young women’s modern contraceptive use in Burkina Faso and Mali from Demographic and Health Survey data

Abstract: BackgroundHigh total fertility rates in Burkina Faso and Mali are leading to population growth beyond the agricultural and fiscal means of its citizens. Providing access to affordable family planning methods is a key step in driving the demographic transition where fertility and mortality rates decline. Furthermore, both nations face significant challenges as climate change is projected to disproportionately impact the western Sahel region undermining environmental, social and economic stability within the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
25
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 9 publications
13
25
4
Order By: Relevance
“…The odds of modern contraceptive utilization among women whose husbands want more children was nearly 25% less likely than the odds of modern contraceptive utilization among women who want the same number of children with their husbands. This is consistent with the evidence from Bangladesh, Burkina Faso and Mali secondary data analysis of Demographic and Health Survey where husband's desired number of children had influenced modern contraceptive utilization among reproductiveage women [20,28]. This could be due to male dominance in decision making autonomy in developing countries including our country, Ethiopia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The odds of modern contraceptive utilization among women whose husbands want more children was nearly 25% less likely than the odds of modern contraceptive utilization among women who want the same number of children with their husbands. This is consistent with the evidence from Bangladesh, Burkina Faso and Mali secondary data analysis of Demographic and Health Survey where husband's desired number of children had influenced modern contraceptive utilization among reproductiveage women [20,28]. This could be due to male dominance in decision making autonomy in developing countries including our country, Ethiopia.…”
Section: Discussionsupporting
confidence: 89%
“…It was also consistent with cross-sectional studies done in Ghana and Ethiopia in 2016 where 21 and 20.8% of reproductive age women used a modern contraceptive method respectively [9,18]. But the current prevalence is higher than the results of secondary data analysis of Nigeria (10.3%) and Mali (15.3%) Demographic and Health Survey which were conducted in 2013 and 2012 respectively [19,20], and lower than the results of secondary data analysis of Burkina Faso (24%) and Afghanistan (25.5%) Demographic and Health Survey which were conducted in 2012 and 2015respectively [20,21]. A cross-sectional multi-country analysis of Demographic and Health Surveys (DHS) conducted between 2008 and 2016 in 52 low and middleincome countries (LMICs) and taking 6857 representative sample from Ethiopia also showed that a prevalence of modern contraceptive method utilization among Ethiopian young reproductive-age women aged between 15 and 24 years was 12.1% which is by far lower than the result from the current study [15].…”
Section: Discussionsupporting
confidence: 84%
“…Findings on the prevalence of modern contraceptive use is in line with the findings obtained in a previous study carried out to examine possible indicators of modern contraceptive use among young women's modern contraceptive use in Burkina Faso and Mali. The study found that in Mali, modern contraceptive use increased from 9.4% in 2001 to 10.2% in 2006 to 15.3% in 2012 [12]. The prevalence in our study also indicates an improvement from the prevalence of 15.3% in 2012, and an indication that the Government of Mali's objective of ensuring an increase in the rate of contraceptive use in Mali, from 9.9% in 2012 to at least 15% by 2018, through the reduction of unmet need for family planning and by targeting teens and young adults (ages 15 to 24) [22] has been met.…”
Section: Discussionmentioning
confidence: 93%
“…Only 16% of married women of reproductive age (15-49 years) used modern contraceptives in 2012 [11]. Among young women, only 15.3% used modern contraceptives in 2012 [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation